Design of Hybrid Energy System for Railway Application (Case Study of People Mover System in Doha, Qatar) - Nugroho, Sri; Mauludin, Luthfi Muhammad; Sirait, Togar; mujiman, mujiman; Sofyan, Ahmad; Tohir, Toto (Jurnal Internasional Penelitian Teknologi Terapan, 2023)
This paper presents the conceptual design of hybrid energy system used in railway application. The hybrid system with batteries and energy storage double-layer capacitor is a new technology that is used under extreme climatic conditions, especially in daytime temperature up to 50°C, high relative humidity, dust and heavy rain. It is a combination of double-layer capacitors and traction batteries. It draws power both externally and from braking energy. In order to reduce CO2 emissions to the environment, energy-saving drives and energy storage are used. Also, in public transportation, Sitras Hybrid Energy System (HES), hybrid energy storage system for trams, has been developed which combines a double-layer capacitor with a nickel-metal hydride battery. The storage not only allows driving without overhead lines, it also enables braking energy to be recovered. A reliable cooling system is required to ensure that the performance of the battery and the capacitor storage is maintained for as long as possible. The results of finite element model showed the robustness for railway application. The computational model refers to proof of static and dynamic strength in accordance with EN12663. A cooling system for a tram using this innovative technology was designed and qualified for the "Qatar Education City People Mover System (PMS)" project.